Dynamic vascular optical spectroscopy for monitoring peripheral arterial disease patients undergoing a surgical intervention - Marone, A.; Maheshwari, N.; Kim, S. K.; Bajakian, D. R.; Hielscher, A. H. (Frontiers in Photonics, 2022)
Peripheral artery disease (PAD) patients experience a reduction in blood supply to the extremities caused by accumulation of plaque in their arterial system. In advanced stages of PAD, surgical intervention is often required to reopen arteries and restore limb perfusion to avoid necrosis and amputations. For a successful intervention it is important to confirm that reperfusion has been reestablished in areas of the foot lacked perfusion before the intervention. The standard procedure to obtain this information is to perform repeated x-ray angiography. However, this approach requires a relatively high radiation dose and an extensive use of contrast agents. To overcome these issues, we suggest the application of dynamic vascular optical spectroscopy (DVOS) for monitoring perfusion in the foot in real-time during the interventions as well as before and after the intervention is completed. In the explorative study presented in this paper, we monitored 10 patients undergoing revascularization surgery. We found that there is a clear change in the DVOS signal when reperfusion to affected areas in the foot is established. It was also possible to assess the effects on the downstream vasculature of balloon inflations and deflations and injection of contrast agents.